Analisis Peran Worklife Balance dan Authentic Leadership Terhadap Job Satisfaction Pada Industri Aviasi - Mohammad Iqbal Ardhalepa Turino; Hendy Tannady (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of Work-Life Balance and Authentic Leadership on Job Satisfaction among employees in the aviation industry. This industry has its own characteristics and challenges, such as high workloads, uncertain work schedules, and strict safety and operational demands, which have the potential to affect work-life balance and the leadership style implemented within the organization. This study uses a quantitative approach with a survey method as a data collection technique, which was distributed to employees in the aviation sector. The data obtained were then analyzed using multiple linear regression techniques to test the relationship between variables. The results of the study indicate that Work-Life Balance and Authentic Leadership have a positive and significant influence on Job Satisfaction. In addition, both variables have been shown to play a role in increasing employee job satisfaction levels. These findings provide practical implications for company management in designing policies that support work-life balance and the implementation of authentic leadership to create a better work environment and improve employee well-being.